Peningkatan Hasil Belajar IPA dengan Menggunakan Pendekatan Konstruktivisme pada Siswa Kelas IV SD Negeri 15 Muaro Takung Kecamatan Kamang Baru - Martina (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2020)
Research is motivated by the fact in elementary schools that learning is often dominated by teachers as a source of information. Based on the experience in the field of student learning outcomes in science is still low, for this reason the researcher through this classroom action research wants to try to improve science learning outcomes by using a constructivism approach to grade IV students of SD Negeri 15 Muara Takung, Kamang Baru sub-district. The approach used is a qualitative approach which consists of two cycles covering four stages, namely planning, acting, observing, reflecting. This research data is in the form of information about the process and data on the results of the action obtained from observations, interviews, and tests. Research subjects were teachers, researchers (practitioners) and fourth grade students, totaling 34 people. Data analysis was performed using qualitative and quantitative data analysis models. The assessments used in data collection were process assessment (affective and psychomotor), outcome assessment (cognitive) and observation sheet signs using the constructivism approach from the teacher and student aspects. To determine the increase in student learning outcomes, tests were held which were analyzed using assessments with a class success benchmark of at least 75%. Student learning outcomes using the constructivism approach in cycles I and II have increased where the average value in cycle I is obtained an average of 73 and in cycle II an average of 83.Thus it can be concluded that learning science using the constructivism approach can improve Science learning outcomes of fourth grade students of SD Negeri 15 Muara Takung.